Nonlinear Super-Resolution Nano-Optics and Applications - Wei, Jingsong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book covers many advances in the subjects of nano-optics and nano photonics. The author describes the principle and technical schematics of common methods for breaking through the optical diffraction limit and focuses on realizing optical super-resolution with nonlinear effects of thin film materials. The applications of nonlinear optical super-resolution effects in nano-data storage, nanolithography, and nano-imaging are also presented. This book is useful to graduate students majoring in optics and nano science and also serves as a reference book for academic researchers, engineers, technical professionals in the fields of super-resolution optics and laser techniques, nano-optics and nano photonics, nano-data storage, nano imaging, micro/nanofabrication and nanolithography and nonlinear optics.
General methods for obtaining nanoscale light spot -- Third-order nonlinear effects -- Characterization methods for nonlinear absorption and refraction coefficients -- Optical nonlinear absorption and refraction of semiconductor thin films -- Nanoscale spot formation through nonlinear refraction effect -- Optical super-resolution effect through nonlinear saturation absorption -- Resolving improvement by combination of pupil filters and nonlinear thin films -- Applications of nonlinear super-resolution thin films in nano-optical data storage -- Applications of nonlinear super-resolution effect in nanolithography and high resolving light imaging -- Remarkings.
Keywords: Physics; Nanoscale science; Nanoscience; Nanostructures; Lasers; Photonics; Optics; Optoelectronics; Plasmons (Physics).; Nanotechnology; Optical materials; Electronic materials; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Laser Technology, Photonics; Nanoscale Science and Technology; Optical and Electronic Materials; Nanotechnology and Microengineering; Electronic books